The effect of substrate disturbance on benthic invertebrates in old-growth broad-leaved forest and planted conifer forest basin streams in Japan. Issue 4 (2nd October 2019) - Yoshimura, Mayumi
ABSTRACT: Disturbances such as heavy rainfall impact benthic invertebrate assemblages in streams and other lotic systems. In temperate Japan, the steep topography means that even modest rainfall can result in significant substrate disturbance. Impacts of this disturbance on benthic invertebrates were examined in the following 1 week and compared in streams of an old-growth broad-leaved forest (OBF) and a planted conifer forest (PCF). Disturbance in this study occurred by kicking the stream substrate. The number of individuals and genera in both forest types decreased after disturbance and gradually recovered over time, but no difference in recovery was observed between the OBF and PCF streams. Benthic invertebrate assemblage composition in both forest types changed depending on the days from disturbance, and differences in recovery between the OBF and PCF streams were observed in the composition of benthic invertebrate assemblages. Recovery patterns of individual taxa after disturbance were also different. Complete recovery was not observed 1 week after disturbance in either forest type, suggesting more time was required to reestablish pre-disturbance invertebrate community composition.